Advanced functional materials for soft robotics: tuning physicochemical properties beyond rigidity control. Issue 4 (31st December 2019) - Calais, Théo; Valdivia y Alvarado, Pablo
Abstract: Reversibility, a key property in materials science and soft matter, is extremely desirable to enable advanced functionality in soft robots. So far, tunable rigidity has attracted most of the attention, notably for its application in novel soft actuators, soft grippers, and its potential impact in locomotion of soft and hybrid robotic devices. Herein, we review recent progress on reversibility in other physicochemical properties which can also play important roles in the functionality of soft robots. We focus on the tunability of five key properties: electrical and thermal conductivities, surface wettability and adhesion, and optical properties. Materials and mechanisms are described, and performances are assessed, when possible, in terms of reversible tunability range, time response, cycling endurance, and power consumption. The potential integration of such solutions to soft robots is systematically discussed.